Transformation of History Learning in the Digital Era: Application of Riau Local History as an Interactive Educational Media - Septiani Chairul Nisa; Ajat Sudrajat; Ardian Fahri (Jurnal Iqra': Kajian Ilmu Pendidikan)
This project aims to create an interactive teaching tool for studying local history, particularly Riau history, using digital technology. The transformation of learning driven by technological developments in the digital era has raised the need for more interesting and relevant learning methods that meet the needs of today’s students. The developed application, Riauxplore, integrates multimedia features such as videos, animations, and interactive quizzes to increase students’ interest in learning about local history. Research and Development (R&D) using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) Model is the research methodology employed. The test involving grade VII students was carried out at SMPN 1 Tempuling, Riau. The Paired Sample T-Test results showed a significant increase in students' interest in learning using the Riauxplore application with a Sig. (2-tailed) value of 0.000, less than 0.05, so H0 was rejected, and Ha was accepted. The average pre-test score of students in the experimental class was 70.56, and the post-test was 84.12, which showed an increase of 13.56. In addition to giving pupils a deeper understanding of local history, this application aids in accomplishing the Sustainable Development Goals (SDGs), particularly those related to high-quality education and cultural preservation. This application provides an innovative way of learning that integrates technology with local history materials. By providing easy access to relevant history learning resources, the app supports a more inclusive and equitable educational process.